Oxidized Hemoglobin Is Antigenic and Immunogenic in Lupus - Jain, Sonia; Bose, Anjali; Bastia, Banajit; Sharma, Hritika; Sachdeva, Ruchi; Jain, Arun K.; Pal, Rahul (Frontiers in Immunology, 2017)
Hemolysis-associated anemia is characteristic of diseases such as atherosclerosis, lupus, malaria, and leishmaniasis; the toxic effects of free hemoglobin (Hb) have been extensively described. This study was based on the premise that release of this sequestered, inflammatory molecule can result in deleterious immunological consequences, particularly in the context of pre-existing lupus. IgG anti-Hb responses were detected in the sera of lupus patients. Lupus-prone mice exhibited heightened plasma Hb levels, and ferric (Fe3+) Hb triggered preferential release of lupus-associated cytokines from splenocytes derived from aging lupus-prone mice. Anti-Hb B cell precursor frequencies were heightened in such mice, which also expressed increased titers of anti-Hb antibodies in serum and in kidney eluates. Fe3+ Hb preferentially increased the functional maturation of bone marrow-derived dendritic cells (BMDCs) from lupus-prone mice, effects abrogated upon the inhibition of Stat3. Hb interacted with lupus-associated autoantigens extruded during apoptosis and coincubation of Hb and apoptotic blebs had additional maturation-inducing effects on lupus BMDCs. Immunization with Hb in lupus-prone mice induced antigen spreading to lupus-associated moieties; Hb-interacting autoantigens were preferentially targeted and increased complement deposition and glomerulosclerosis were observed. Hb therefore demonstrates both antigenicity and immunogenicity and triggers specific immuno-pathological effects in a lupus milieu.